The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1007/s00417-013-2275-x
|View full text |Cite
|
Sign up to set email alerts
|

Adalimumab for juvenile idiopathic arthritis-associated uveitis

Abstract: Adalimumab showed to be effective and relatively safe for treatment of JIA-associated uveitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
23
2
2

Year Published

2014
2014
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(31 citation statements)
references
References 28 publications
4
23
2
2
Order By: Relevance
“…In particular, 2 retrospective studies reported a good response rate on uveitis (57% and 76%) in patients with JIA treated with ADA 7,8 . However, in neither study was it possible to extract specific outcomes in the subset of patients who received ADA as first-line biologic treatment.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, 2 retrospective studies reported a good response rate on uveitis (57% and 76%) in patients with JIA treated with ADA 7,8 . However, in neither study was it possible to extract specific outcomes in the subset of patients who received ADA as first-line biologic treatment.…”
Section: Discussionmentioning
confidence: 99%
“…All of them were observational in design (three case series; [106][107][108] one Italian registry-based study; 109 one comparative cohort study 110 ), and all assessed treatment with adalimumab (with one also assessing infliximab 110 in uveitis patient populations with varying proportions of JIA uveitis. We have not performed an independent critical appraisal of these studies in this assessment report.…”
Section: Clinical Effectivenessmentioning
confidence: 99%
“…Similar findings have been reported by several reports. 28,29,35 We should highlight that our patients were previously biologically naive, which might explain the high efficacy obtained. This is in accordance with the data of Simonini et al, 37 who also demonstrated better efficacy of adalimumab when used as a first anti-TNF-alpha treatment in chronic childhood uveitis.…”
Section: Discussionmentioning
confidence: 96%
“…Different authors have reported the same findings. 35,36 The ongoing SYCAMORE trial has been investigating the clinical effectiveness and safety of dual adalimumab and methotrexate treatment of JIA associated uveitis. 6 Our results have shown no new flares or worsening of visual acuity and only two patients had monocular visual loss, which was already present before starting adalimumab treatment.…”
Section: Discussionmentioning
confidence: 99%